Alpha retinal ganglion cells in pigmented mice retina: number and distribution - Gallego-Ortega, Alejandro; Norte-Muñoz, María; Di Pierdomenico, Johnny; Avilés-Trigueros, Marcelino; de la Villa, Pedro; Valiente-Soriano, Francisco Javier; Vidal-Sanz, Manuel (Frontiers in Neuroanatomy, 2022)
Purpose: To identify and characterize numerically and topographically the population of alpha retinal ganglion cells (αRGCs) and their subtypes, the sustained-response ON-center αRGCs (ONs-αRGCs), which correspond to the type 4 intrinsically photosensitive RGCs (M4-ipRGCs), the transient-response ON-center αRGCs (ONt-αRGCs), the sustained-response OFF-center αRGCs (OFFs-αRGCs), and the transient-response OFF-center αRGCs (OFFt-αRGCs) in the adult pigmented mouse retina. Methods: The αRGC population and its subtypes were studied in flat-mounted retinas and radial sections immunodetected against non-phosphorylated high molecular weight neurofilament subunit (SMI-32) or osteopontin (OPN), two αRGCs pan-markers; Calbindin, expressed in ONs-αRGCs, and amacrines; T-box transcription factor T-brain 2 (Tbr2), a key transcriptional regulator for ipRGC development and maintenance, expressed in ipRGCs and GABA-displaced amacrine cells; OPN4, an anti-melanopsin antibody; or Brn3a and Brn3c, markers of RGCs. The total population of RGCs was counted automatically and αRGCs and its subtypes were counted manually, and color-coded neighborhood maps were used for their topographical representation. Results: The total mean number of αRGCs per retina is 2,252 ± 306 SMI32+αRGCs and 2,315 ± 175 OPN+αRGCs (n = 10), representing 5.08% and 5.22% of the total number of RGCs traced from the optic nerve, respectively. αRGCs are distributed throughout the retina, showing a higher density in the temporal hemiretina. ONs-αRGCs represent ≈36% [841 ± 110 cells (n = 10)] of all αRGCs and are located throughout the retina, with the highest density in the temporal region. ONt-αRGCs represent ≈34% [797 ± 146 cells (n = 10)] of all αRGCs and are mainly located in the central retinal region. OFF-αRGCs represent the remaining 32% of total αRGCs and are divided equally between OFFs-αRGCs and OFFt-αRGCs [363 ± 50 cells (n = 10) and 376 ± 36 cells (n = 10), respectively]. OFFs-αRGCs are mainly located in the supero-temporal peripheral region of the retina and OFFt-αRGCs in the mid-peripheral region of the retina, especially in the infero-temporal region. Conclusions: The combination of specific antibodies is a useful tool to identify and study αRGCs and their subtypes. αRGCs are distributed throughout the retina presenting higher density in the temporal area. The sustained ON and OFF response subtypes are mainly located in the periphery while the transient ON and OFF response subtypes are found in the central regions of the retina.